Preparation method and application of carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst

The synthetic carbon-nitrogen sulfur-doped cobalt ferrate modified mesoporous silicon catalyst was solved by the "grinding-calcination" method, and the problems of low degradation efficiency, long time, large amount of dosing and narrow pH range of the prior art mesoporous silicon catalysts were solved. It achieves efficient and rapid degradation of sulfonamide antibiotics and has good reusability.

CN119488932AActive Publication Date: 2025-02-21CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411634918.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In the prior art, mesoporous silicon catalysts have low degradation efficiency in the process of activating persulfate degradation of sulfonamide antibiotics, have too long degradation time, excessive amounts of catalyst and persulfate are added, and the pH range is narrow.

Method used

The "grinding-calcination" method was used to synthesize carbon-nitrogen sulfur-doped cobalt ferrate modified mesoporous silicon catalyst, by combining alkyl quaternary ammonium salts, anhydrous ethanol, ammonium hydroxide and inorganic silicon sources with cobalt ferrate particles and sulfur-containing After the amino acid is ground in a mortar, it is calcined in a nitrogen atmosphere to obtain a carbon-nitrogen sulfur-doped cobalt ferrate modified mesoporous silicon catalyst.

Benefits of technology

Improve the activation efficiency of persulfate, significantly improve the degradation efficiency of sulfonamide antibiotics, shorten the degradation time, reduce the amount of catalyst and persulfate added, expand the scope of pH application, and realize the repeatability of catalysts use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488932A_ABST
    Figure CN119488932A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst. The preparation method comprises the following steps: sequentially adding alkyl quaternary ammonium salt, absolute ethyl alcohol, ammonium hydroxide and an inorganic silicon source into water, uniformly stirring, and naturally precipitating; separating the precipitate, removing the template agent, cleaning and drying to obtain mesoporous silicon; mesoporous silicon, cobalt ferrite particles and sulfur-containing amino acid are fully ground and then calcined under protective gas, and the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst can be obtained. The prepared material has the advantages of being simple in preparation and convenient to operate, meanwhile, based on the multi-element synergistic effect of carbon, nitrogen, sulfur and cobalt ferrite, the electron transfer rate can be further increased, the persulfate activation efficiency is improved, and the application prospect is wide. In a sulfonamide antibiotic removal system, the method has the advantages of high degradation efficiency, short degradation time, small dosage of a catalyst and persulfate, wide pH adaptability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and application of mesoporous silicon derivative catalysts, and specifically discloses a preparation method and application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst. Background Art

[0002] Sulfonamide antibiotics are a class of drugs widely used in the treatment of human and animal diseases and infections. Due to the limited removal of sulfonamide antibiotics by existing sewage treatment plants, sulfonamide antibiotics have been frequently detected in secondary effluents, groundwater and surface water of sewage treatment plants in recent years. Sulfonamide antibiotics have a long half-life, biotoxicity and bioaccumulation, posing a serious threat to human health and aquatic life. Therefore, effective methods are urgently needed to remove sulfonamide antibiotics from water.

[0003] The advanced oxidation process based on persulfate is widely used in the removal of sulfonamide antibiotics due to its simple operation, safe and convenient transportation and strong oxidizing property. Spinel metal cobalt ferrite is considered to be one of the better materials for activating persulfate due to its strong magnetization strength and low cost. The doping of non-metallic carbon, nitrogen or sulfur elements can accelerate the electron transfer in the reaction process, improve the activation efficiency of the catalyst for persulfate, and thus improve the degradation efficiency of sulfonamide antibiotics. However, since cobalt ferrite is easy to agglomerate, resulting in a reduction in active sites, the degradation efficiency of persulfate activated by doping with carbon, nitrogen or sulfur elements for sulfonamide antibiotics is not ideal, and there are problems such as low degradation efficiency, long degradation time, excessive catalyst and persulfate dosage, and narrow pH application range. Mesoporous silica molecular sieve materials have a large specific surface area, rich and regular pore structure, and strong chemical stability, making them ideal catalyst carriers. However, at present, the preparation methods of modified mesoporous silica mostly use hydrothermal method, coprecipitation method, etc. These methods often have problems such as complex operation, excessive waste liquid generation and long synthesis cycle. Therefore, choosing a suitable and simple loading method to simultaneously load non-metallic and bimetallic cobalt ferrite materials on mesoporous silica molecular sieve materials can improve the activation efficiency of persulfate, thereby enhancing the removal efficiency of sulfonamide antibiotics. This has a strong practical significance for the research on the removal of sulfonamide antibiotics in water environments and the expansion of mesoporous silica materials in the field of water pollution control. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, aiming to solve the problems of low degradation efficiency, long degradation time, excessive addition of catalyst and persulfate, narrow pH application range, etc. of the mesoporous silicon catalyst in the prior art in the process of activating persulfate to degrade sulfonamide antibiotics. The second purpose of the present invention is to provide an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst to remove organic pollutants such as sulfonamide antibiotics.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a carbon-nitrogen-sulfur doped carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, characterized in that it comprises the following steps: 1): Add alkyl quaternary ammonium salt, anhydrous ethanol, ammonium hydroxide and inorganic silicon source into water, stir evenly and let stand; 2): Separate the white solid obtained by natural precipitation after standing, remove the alkyl quaternary ammonium salt, and obtain the mesoporous silicon material after washing and drying; 3): Place the mesoporous silicon material, cobalt ferrite particles and sulfur-containing amino acid in a mortar and grind for the time required by the process; 4): The ground material is calcined in a protective atmosphere to obtain a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst.

[0006] Furthermore, in the step 1), the mass ratio of the alkyl quaternary ammonium salt to water is 0.325-0.45:50, and the volume ratio of the anhydrous ethanol, ammonium hydroxide, inorganic silicon source and water is 20-28:7-9:1.5-2.5:70-90.

[0007] Furthermore, in the step 1), the stirring time is 30 min to 120 min, and the standing time is 12-20 h.

[0008] Furthermore, the method for removing the alkyl quaternary ammonium salt in step 2) is any one of a solvent reflux method, a calcination method or a microwave method.

[0009] Furthermore, in the step 3), the mass ratio of mesoporous silicon, cobalt ferrite and sulfur-containing amino acid is 0.5:0.70~0.25:0.25~0.70.

[0010] Furthermore, in step 3), the grinding time in the mortar is 30 to 90 minutes.

[0011] Furthermore, in the step 4), calcination is carried out in a nitrogen atmosphere, the calcination temperature is 500-600° C., the heating rate is 2-5° C. / min, and the holding time is 3.5-6.5 h.

[0012] An application of a carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst prepared by the aforementioned preparation method of a carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst, characterized in that it is applied to remove sulfonamide antibiotics in an aquatic environment.

[0013] Furthermore, the specific steps of applying the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst to the degradation of sulfonamide antibiotics are as follows: adding the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst to the sulfonamide antibiotic solution, and then adding persulfate to start the degradation reaction; after the reaction is completed, using an external magnetic field to separate the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst material, and after washing and drying with water, it can be reused.

[0014] Furthermore, the persulfate is any one of potassium persulfate, sodium persulfate, potassium hydrogen persulfate, and sodium hydrogen persulfate, or any two of them are mixed in a ratio greater than 0%, or any three of them are mixed in a ratio greater than 0%, or four of them are mixed in a ratio greater than 0%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The "grinding-calcination" method for synthesizing the loading method of carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst provided by the present invention simplifies the operation steps, avoids the generation of waste liquid during the carbon-nitrogen-sulfur and cobalt ferrite loading process, and shortens the synthesis cycle.

[0016] 2. The present invention adopts the "grinding-calcination" method to synthesize the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, which can successfully load the sulfur-containing amino acid and cobalt ferrite on the mesoporous silicon material, and effectively overcome the disadvantage that cobalt ferrite is easy to agglomerate and deactivate, and realizes the advantage of carbon, nitrogen, sulfur, and cobalt ferrite synergistically accelerating electron transfer, effectively improving the activation efficiency of persulfate.

[0017] 3. The carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared by the present invention has high degradation efficiency, short degradation time, small amount of catalyst and persulfate added, and wide pH application range in the application of efficient activation of persulfate to remove sulfonamide antibiotics.

[0018] 4. The carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared by the present invention can realize material recovery by means of an external magnetic field, and can be recycled after simple rinsing and drying, and still has good efficiency in activating persulfate to degrade sulfonamide antibiotics when continuously recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 X-ray diffraction patterns of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the mesoporous silicon and cobalt ferrite prepared in Comparative Example 1.

[0020] Figure 2 Raman spectra of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the carbon, nitrogen and sulfur material prepared in Comparative Example 1.

[0021] Figure 3Field emission scanning electron microscope images of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the mesoporous silicon prepared in Comparative Example 1.

[0022] Figure 4 This is an energy dispersion spectrum of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention.

[0023] Figure 5 High-resolution transmission electron microscopy images of the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the mesoporous silicon, cobalt ferrite and carbon-nitrogen-sulfur materials prepared in Comparative Example 1.

[0024] Figure 6 This is a hysteresis regression curve diagram of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention.

[0025] Figure 7 The performance diagram of removing sulfamethoxazole by the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the mesoporous silicon, cobalt ferrite, carbon-nitrogen-sulfur, cobalt ferrite-mesoporous silicon, carbon-nitrogen-sulfur-mesoporous silicon and carbon-nitrogen-sulfur-cobalt ferrite prepared in Comparative Example 1.

[0026] Figure 8 This is a graph showing the removal efficiency of sulfamethoxazole by the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention and the carbon-doped cobalt ferrite modified mesoporous silicon catalyst and the carbon-nitrogen doped cobalt ferrite modified mesoporous silicon catalyst prepared in Comparative Example 2.

[0027] Fig. 9 This is an efficiency diagram of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention for activating potassium persulfate to degrade sulfamethoxazole at different dosages.

[0028] Fig.10 This is an efficiency diagram of the degradation of sulfamethoxazole by activating different concentrations of potassium persulfate with the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention.

[0029] Fig.11 This is an efficiency diagram of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention for activating potassium persulfate to degrade sulfamethoxazole at different pH values.

[0030] Fig.12 This is a cyclic regeneration performance diagram of the degradation of sulfamethoxazole by activating potassium persulfate with the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1 of the present invention.

[0031] Fig.13 This is an efficiency diagram of the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst activated with potassium persulfate to degrade sulfamethoxazole in different actual water bodies prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In the following, some embodiments of the present invention are described in detail in conjunction with the accompanying drawings, and the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0033] The present invention provides a method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, comprising the following steps: 1): Add alkyl quaternary ammonium salt, anhydrous ethanol, ammonium hydroxide and inorganic silicon source into water, stir evenly and let stand for the time required by the process; These components will react chemically when added. The inorganic silicon source will hydrolyze and crosslink around the template alkyl quaternary ammonium salt under the alkaline conditions created by ammonium hydroxide, thereby forming a mesoporous silicon material containing a template with a hexagonal liquid crystal phase structure. The addition of anhydrous ethanol can change the hydrolysis and crosslinking rate of the silicon source, so that the mesoporous silicon molecular sieve material forms spherical particles.

[0034] 2): Separate the white solid obtained by natural precipitation after standing, remove the alkyl quaternary ammonium salt retained in the white solid particles, wash and dry to obtain a mesoporous silicon material; The above components react chemically to produce a white precipitate, which is separated to obtain a white solid. The alkyl quaternary ammonium salt acts as a template, and orderly channels can be obtained by removing the template.

[0035] 3): Place the mesoporous silicon material, cobalt ferrite particles and sulfur-containing amino acids (such as cysteine, methionine, and cysteine) in a mortar and grind for the time required by the process; 4): The ground material is calcined in a protective atmosphere to obtain a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst.

[0036] Furthermore, in step 1), the mass ratio of the alkyl quaternary ammonium salt to water is 0.325-0.45:50, and the volume ratio of the anhydrous ethanol, ammonium hydroxide, inorganic silicon source and water is 20-28:7-9:1.5-2.5:70-90.

[0037] Furthermore, in step 1), the stirring time is 30 to 150 minutes, and the natural sedimentation time is 12 to 20 hours.

[0038] Furthermore, in step 2), any one of solvent reflux method, calcination method and microwave method is used to remove the alkyl quaternary ammonium salt to obtain the mesoporous silicon material.

[0039] Furthermore, in step 3), the mass ratio of the mesoporous silicon material, cobalt ferrite and sulfur-containing amino acid is 0.5:0.70~0.25:0.25~0.70.

[0040] Furthermore, in step 3), the grinding time in the mortar is 30-90 minutes.

[0041] Furthermore, in step 4), the carbon, nitrogen and sulfur doped cobalt ferrite mesoporous silicon catalyst is calcined in a nitrogen atmosphere at a temperature of 500-600° C., a heating rate of 2-5° C. / min, and a holding time of 3.5-6.5 h.

[0042] The carbon-nitrogen-sulfur-doped cobalt ferrite-modified mesoporous silicon catalyst for efficiently activating persulfate prepared by the above method is used in the degradation of sulfonamide antibiotics, an organic pollutant in water.

[0043] Furthermore, the specific steps of using the above method to prepare a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst for degrading sulfonamide antibiotics, an organic pollutant in water, are as follows: adding the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon of the present invention as a catalyst to a sulfonamide antibiotic solution, then adding persulfate to start the degradation reaction, and after the reaction is completed, separating the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst with an external magnetic field, and then washing and drying it for reuse.

[0044] Furthermore, the persulfate is any one of potassium persulfate, sodium persulfate, potassium hydrogen persulfate or sodium hydrogen persulfate, or any two of them are mixed in a ratio greater than 0%, or any three of them are mixed in a ratio greater than 0%, or four of them are mixed in a ratio greater than 0%.

[0045] Example 1 This embodiment provides a method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: (1) Add 3.0 g of alkyl quaternary ammonium salt, 125 mL of anhydrous ethanol, 40 mL of ammonium hydroxide and 10 mL of ethyl orthosilicate to 400 mL of water, stir for 30 min, and allow to precipitate naturally for 12 h.

[0046] (2) Separate the naturally precipitated white solid, weigh the dried white solid and place it in a tube furnace. Calcinate it at 550°C for 5 h in an air atmosphere. Wash the calcined material and dry it at 60°C to obtain a mesoporous silicon material.

[0047] (3) Add 1.0 g of mesoporous silica, 0.56 g of cobalt ferrite particles, and 1.12 g of cysteine ​​into a mortar and grind thoroughly for 30 min.

[0048] (4) The ground mixed material is placed in a tubular furnace and calcined at 550 °C for 5 h at a heating rate of 2 °C / min under the protection of a nitrogen atmosphere. After the material is taken out, a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst (C / N / S / CFO / Si) is obtained.

[0049] Comparative Example 1 Mesoporous silicon is the mesoporous silicon material obtained in step (2) of Example 1. Cobalt ferrite (CFO) is a commercial reagent and is used directly. The carbon-nitrogen-sulfur material is prepared by grinding cysteine ​​and calcining it under the same conditions as step (4) of Example 1. The difference between the preparation method of cobalt ferrite-mesoporous silicon material and the steps of Example 1 is that in step (3), 1.0g of mesoporous silicon and 0.56g of cobalt ferrite particles are fully ground for 30min, and the other steps are the same as Example 1. The difference between the preparation method of carbon-nitrogen-sulfur-mesoporous silicon material and the steps of Example 1 is that in step (3), 1.0g of mesoporous silicon and 1.12g of cysteine ​​are fully ground for 30min, and the other steps are the same as Example 1. The difference between the preparation method of carbon-nitrogen-sulfur-cobalt ferrite material and the steps of Example 1 is that in step (3), 0.56g of cobalt ferrite particles and 1.12g of cysteine ​​are fully ground for 30min, and the other steps are the same as Example 1.

[0050] Figure 1 The X-ray diffraction diagrams of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and the mesoporous silicon, cobalt ferrite and carbon, nitrogen and sulfur materials in Comparative Example 1. Figure 1 It can be seen that the diffraction peaks of mesoporous silicon material appear near 2θ=20-25°, and the diffraction peaks of cobalt ferrite appear near 2θ=18.6°, 30.0°, 35.2°, 43.1°, 53.3°, 57.2°, and 62.7° (PDF#22-1086), corresponding to the (111), (220), (311), (400), (422), (511), and (440) crystal planes of cobalt ferrite, respectively. The X-ray diffraction pattern of carbon, nitrogen, and sulfur doped cobalt ferrite modified mesoporous silicon catalyst shows the same characteristic peaks as mesoporous silicon and cobalt ferrite, and the peak angle remains unchanged, indicating that cobalt ferrite is successfully loaded on mesoporous silicon.

[0051] Figure 2 The Raman spectra of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and the carbon, nitrogen and sulfur material in Comparative Example 1. -1 The D peak at 1580 cm represents incomplete carbon atoms with many structural defects. -1 The G peak at represents the degree of graphitization of the material. D / I G The value is used to indicate the disorder and defect structure of carbon materials. The larger the value, the higher the disorder of the carbon material and the more defect structures it has. Figure 2It can be seen that the I D / I G The value is greater than the I of carbon-nitrogen-sulfur materials D / I G Value, I D / I G The increase in the value indicates that more carbon atom crystal defect structures are formed, which is conducive to the formation of more catalytic active sites, promoting the activation of persulfate and thus achieving the removal of sulfonamide antibiotics.

[0052] Figure 3 The field emission scanning electron micrographs of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and the mesoporous silicon, cobalt ferrite and carbon, nitrogen and sulfur materials in Comparative Example 1. Figure 3 It can be seen that mesoporous silicon presents a dispersed and uniform spherical morphology; the surface of cobalt ferrite is rough and the agglomeration phenomenon is relatively serious; the carbon-nitrogen-sulfur material presents a blocky morphology with fewer surface defects. The carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst successfully retains the spherical morphology characteristics of the mesoporous silicon material. Figure 4 is the energy dispersion spectrum of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1, Figure 4 It can be seen that iron, cobalt, oxygen, carbon, nitrogen, sulfur and silicon elements were detected on the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1, proving that cobalt ferrite and carbon, nitrogen and sulfur were successfully loaded on mesoporous silicon.

[0053] Figure 5 The high-resolution transmission electron microscopy images of the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and the mesoporous silicon in Comparative Example 1 are shown. Figure 5 a It can be seen that mesoporous silica has an ordered pore structure; Figure 5 b and Figure 5 The gray circles on c represent mesoporous silicon materials, and the black particles represent cobalt ferrite particles. Figure 5 The gray strips on d represent carbon layers. Figure 5 b, c, d show that the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst retains the ordered pores of the mesoporous silicon material, evenly disperses the cobalt ferrite particles, and generates a carbon layer.

[0054] Figure 6 is the hysteresis regression curve of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1. Figure 6 It can be seen that the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst is magnetic, and the saturation magnetization (Ms) is 10.98 emu / g, which is conducive to the rapid separation of materials from the aqueous solution after completing the degradation experiment.

[0055] Sulfamethoxazole is a representative class of sulfonamide antibiotics, which is also widely detected in water bodies. Therefore, sulfamethoxazole is selected as a representative to test the degradation performance of the catalyst prepared by the present invention on sulfonamide antibiotics. 5 mg of the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and mesoporous silicon, cobalt ferrite, carbon-nitrogen-sulfur, cobalt ferrite-mesoporous silicon, carbon-nitrogen-sulfur-mesoporous silicon and carbon-nitrogen-sulfur-cobalt ferrite in Comparative Example 1 were added to 100 mL of sulfamethoxazole solution, and the initial concentration of sulfamethoxazole was 10 mg / L. 0.15 mmol / L of potassium persulfate (PMS) was added to start the degradation reaction. The initial pH of the solution was 7. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was measured.

[0056] like Figure 7 It can be seen that the adsorption rates of sulfamethoxazole for mesoporous silicon, cobalt ferrite, carbon-nitrogen-sulfur, cobalt ferrite-mesoporous silicon, carbon-nitrogen-sulfur-mesoporous silicon, carbon-nitrogen-sulfur-cobalt ferrite and carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalysts for sulfamethoxazole in 10 min were all less than 10%, indicating that the above materials have weak adsorption properties for sulfamethoxazole at this dosage. The removal rate of sulfamethoxazole for PMS alone in 10 min was 11.29%, and the removal rates of sulfamethoxazole for mesoporous silicon, cobalt ferrite, carbon-nitrogen-sulfur, cobalt ferrite-mesoporous silicon, carbon-nitrogen-sulfur-mesoporous silicon, and carbon-nitrogen-sulfur-cobalt ferrite activated PMS were 10.73%, 25.47%, 20.58%, 38.72%, 20.01% and 44.62%, respectively. However, the removal rate of sulfamethoxazole by CNS-doped cobalt ferrite modified mesoporous silica activated PMS can reach 96.63%, which indicates that the simultaneous loading of CNS and cobalt ferrite on mesoporous silica materials can significantly improve the degradation performance of sulfamethoxazole.

[0057] Comparative Example 2 This embodiment provides an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: In step (3) of Example 1, cysteine ​​is replaced by sucrose, and the other steps and conditions in Example 1 remain unchanged, thereby obtaining a carbon-doped cobalt ferrite modified mesoporous silicon catalyst (C / CFO / Si). In step (3) of Example 1, cysteine ​​is replaced by L-histidine, and the other steps and conditions in Example 1 remain unchanged, thereby obtaining a carbon-nitrogen-doped cobalt ferrite modified mesoporous silicon catalyst (C / N / CFO / Si).

[0058] 5 mg of the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst in Example 1 and 5 mg of the carbon-doped cobalt ferrite modified mesoporous silicon material and carbon-nitrogen doped cobalt ferrite modified mesoporous silicon material in Comparative Example 2 were dispersed in 100 mL of sulfamethoxazole solution, the initial concentration of sulfamethoxazole was 10 mg / L, and 0.15 mmol / L of PMS was added to start the degradation reaction. The initial pH of the solution was 7. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was determined by high performance liquid chromatography.

[0059] like Figure 8 It can be seen that the adsorption rates of sulfamethoxazole on carbon-doped cobalt ferrite modified mesoporous silicon catalyst, carbon-nitrogen doped cobalt ferrite modified mesoporous silicon catalyst and carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst are all less than 10%. The removal rate of sulfamethoxazole by PMS in 10 minutes is 11.29%. The removal rates of sulfamethoxazole by carbon-doped cobalt ferrite modified mesoporous silicon catalyst, carbon-nitrogen doped cobalt ferrite modified mesoporous silicon catalyst and carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst activated by PMS are 50.24%, 56.37% and 96.63%, respectively, which shows that the simultaneous doping of carbon, nitrogen and sulfur can significantly improve the efficiency of activating PMS to degrade sulfamethoxazole compared with carbon doping and carbon-nitrogen doping.

[0060] Example 2 This embodiment provides an application of a carbon, nitrogen and sulfur doped cobalt ferrite mesoporous silicon catalyst, the steps are as follows: 3 mg, 5 mg, 10 mg and 20 mg of the carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst obtained in Example 1 were dispersed in 100 mL of different sulfamethoxazole solutions, and the initial concentration of sulfamethoxazole was 10 mg / L. 0.15 mmol / L of PMS was added to start the degradation reaction. The initial pH of the solution was 7. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was determined by high performance liquid chromatography.

[0061] like Fig. 9 It can be seen that the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silica catalyst can complete the degradation of sulfamethoxazole in 10 minutes at different dosages (3 mg, 5 mg, 10 mg and 20 mg), and the removal rates are 90.38%, 96.39%, 96.71% and 97.95%, respectively, indicating that the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silica catalyst can efficiently activate PMS to degrade sulfamethoxazole even at low dosages.

[0062] Example 3 This embodiment provides an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: 5 mg of the carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst obtained in Example 1 was dispersed in 100 mL of sulfamethoxazole solution, and the initial concentration of sulfamethoxazole was 10 mg / L. Then 0.10 mmol / L, 0.15 mmol / L, 0.20 mmol / L and 0.30 mmol / L of PMS were added to start the degradation reaction. The initial pH of the solution was 7. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was measured.

[0063] like Fig.10 It can be seen that the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silica catalyst can complete the degradation of sulfamethoxazole in 10 minutes at different PMS concentrations (0.10mmol / L, 0.15mmol / L, 0.20mmol / L and 0.30mmol / L), and the removal rates are 90.04%, 96.39%, 95.71% and 96.61%, respectively. This indicates that the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silica catalyst can efficiently activate PMS to degrade sulfamethoxazole at lower PMS concentrations.

[0064] Example 5 This embodiment provides an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: 5 mg of the carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst obtained in Example 1 was dispersed in 100 mL of sulfamethoxazole solution, the initial concentration of sulfamethoxazole was 10 mg / L, and then 0.15 mmol / L of PMS was added to start the degradation reaction. The pH of the reaction system was 5, 7 and 9, respectively. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was measured.

[0065] like Fig.11 It can be seen that when the pH of the sulfamethoxazole solution is 5, 7, and 9, the carbon, nitrogen, and sulfur doped cobalt ferrite modified mesoporous silica catalyst can complete the degradation reaction within 10 min, and the removal rates are 94.25%, 96.40%, and 94.14%, respectively, indicating that the carbon, nitrogen, and sulfur doped cobalt ferrite modified mesoporous silica catalyst can activate PMS in a wide pH range to effectively remove sulfamethoxazole.

[0066] Example 4 This embodiment provides an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: 5 mg of the carbon, nitrogen, and sulfur-doped cobalt ferrite modified mesoporous silicon catalyst obtained in Example 1 was dispersed in 100 mL of sulfamethoxazole solution, the initial concentration of sulfamethoxazole was 10 mg / L, and 0.15 mmol / L of PMS was added to start the degradation reaction. The initial pH of the solution was 7. After the reaction was completed, the carbon, nitrogen, and sulfur-doped cobalt ferrite modified mesoporous silicon catalyst was separated by an external magnetic field, washed with water, and then dried for reuse.

[0067] like Fig.12 As shown, after three cycles of recycling, the removal rate of sulfamethoxazole by activated PMS of carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst is still 79.59%, indicating that carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silicon catalyst has good regeneration and reuse.

[0068] Example 5 This embodiment provides an application of a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, the steps are as follows: 5 mg of the carbon-nitrogen-sulfur-doped cobalt ferrite modified mesoporous silica catalyst obtained in Example 1 was added to 100 mL of sulfamethoxazole solution in actual water (tap water, lake water and secondary effluent from a sewage treatment plant), with an initial concentration of sulfamethoxazole of 10 mg / L, and then 0.15 mmol / L of PMS was added to start the degradation reaction. After the reaction was completed, the concentration of the remaining sulfonamide antibiotics in the solution was measured.

[0069] like Fig.13 It can be seen that the removal of sulfamethoxazole in actual water bodies (tap water, lake water and secondary effluent from sewage treatment plants) by carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silica catalyst activated with PMS was also completed within 10 minutes, and the removal rate was above 89.24%, indicating that the carbon, nitrogen and sulfur doped cobalt ferrite mesoporous silica catalyst is highly efficient in removing sulfamethoxazole in actual water bodies.

[0070] Embodiment 6-11 The preparation methods of the catalysts in Examples 6-11 are the same as those in Example 1, except that some parameters are different, as shown in the following table: Examples 8-13 prepared carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalysts. After testing, the removal effect of activated PMS on sulfamethoxazole degradation was comparable to that of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared in Example 1.

[0071] The above are only several embodiments and comparative examples of the present invention, which cannot be used to limit the scope of the rights of the present invention in any form. Any technician familiar with the art, without departing from the scope of the technical rights of the present invention, using all or part of the processes of the above-described embodiments and comparative examples to make changes or modifications are equivalent to equivalent implementation cases and comparative cases, and all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst, characterized in that: The following steps are involved: 1): Add alkyl quaternary ammonium salt, anhydrous ethanol, ammonium hydroxide and inorganic silicon source into water, stir evenly and let stand; The white solid obtained by natural precipitation after standing is separated, the alkyl quaternary ammonium salt is removed, and the mesoporous silicon material is obtained after washing and drying; 3): Place the mesoporous silicon material, cobalt ferrite particles and sulfur-containing amino acid in a mortar and grind for the time required by the process; 4): The ground material is calcined in a protective atmosphere to obtain a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst.

2. The method for preparing the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: In the step 1), the mass ratio of the alkyl quaternary ammonium salt to water is 0.325-0.45:50, and the volume ratio of the anhydrous ethanol, ammonium hydroxide, inorganic silicon source and water is 20-28:7-9:1.5-2.5:70-90.

3. The method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: In the step 1), the stirring time is 30 min to 120 min, and the standing time is 12-20 h.

4. The method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: The method for removing the alkyl quaternary ammonium salt in step 2) is any one of solvent reflux method, calcination method or microwave method.

5. The method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: In the step 3), the mass ratio of mesoporous silicon, cobalt ferrite and sulfur-containing amino acid is 0.5:0.70-0.25:0.25-0.

70.

6. The method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: The grinding time in the mortar in step 3) is 30 to 90 minutes.

7. The method for preparing a carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 1, characterized in that: In the step 4), calcination is carried out in a nitrogen atmosphere, the calcination temperature is 500-600° C., the heating rate is 2-5° C. / min, and the holding time is 3.5-6.5 h.

8. An application of a carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared by the preparation method of a carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst as claimed in any one of claims 1 to 7, characterized in that: Used to remove sulfonamide antibiotics in water environments.

9. Use of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared by the preparation method of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 8, characterized in that: The specific steps of applying the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst to the degradation of sulfonamide antibiotics are as follows: adding the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst to the sulfonamide antibiotic solution, and then adding persulfate to start the degradation reaction; after the reaction is completed, using an external magnetic field to separate the carbon-nitrogen-sulfur doped cobalt ferrite modified mesoporous silicon catalyst material, and washing and drying with water.

10. Use of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst prepared by the preparation method of the carbon, nitrogen and sulfur doped cobalt ferrite modified mesoporous silicon catalyst according to claim 9, characterized in that: The persulfate is any one of potassium persulfate, sodium persulfate, potassium hydrogen persulfate, and sodium hydrogen persulfate, or any two of them are mixed in a ratio greater than 0%, or any three of them are mixed in a ratio greater than 0%, or four of them are mixed in a ratio greater than 0%.

Citation Information

Patent Citations

  • Cobalt ferrite / montmorillonite / C catalyst capable of efficiently activating persulfate as well as preparation method and application of cobalt ferrite / montmorillonite / C catalyst

    CN112473670A

  • Nitrogen-and-sulfur co-doped ordered mesoporous carbon material as well as preparation method and application thereof

    CN113171785A

  • Nitrogen-doped cobalt iron / carbon catalyst capable of efficiently activating persulfate as well as preparation method and application of nitrogen-doped cobalt iron / carbon catalyst

    CN113333007A